The Ongoing Challenges of Hearing Loss: Stigma, Socio-Cultural Differences, and Accessibility Barriers - Mirko Aldè; Umberto Ambrosetti; Stefania Barozzi; Samantha Aldè (Audiology Research)
Background/Objectives: Hearing loss (HL) is a prevalent condition that can lead to social exclusion. This review explores the epidemiological, cultural, and social dimensions of HL and examines the barriers to accessibility that individuals with HL encounter. Methods: This research employs a narrative review approach to provide a comprehensive overview of HL, focusing on stigma, gender disparities, cultural and social differences, and accessibility challenges. Results: The review highlights pervasive prejudices surrounding HL and hearing devices. Gender disparities are evident, with Deaf women facing compounded challenges. Cultural perspectives on HL differ widely, ranging from the medical model, which emphasizes treatment using hearing devices, to the Deaf community’s social model, which views deafness as a cultural identity. Socioeconomic disparities further restrict access to modern technologies, particularly in low-income settings, while intersectional discrimination affects marginalized groups within the Deaf community. Public spaces also present significant barriers related to communication, architecture, and technology, which hinder accessibility for individuals with HL. Conclusions: A cultural shift is essential to dismantle societal stereotypes and reduce discrimination associated with HL. Moreover, improving accessibility for individuals with HL necessitates a multifaceted approach, including accessible design, staff training, and the integration of assistive technologies.